Role of microRNA-124 in cardiomyocyte hypertrophy inducedby angiotensin II - Bao, Q.; Chen, L.; Li, J.; Zhao, M.; Wu, S.; Wu, W.; Liu, X. (Cellular and Molecular Biology, 2017)
Cardiac hypertrophy is a crucial predictor of heart failure and is regulated by microRNAs. MicroRNA-124 (miR-124) is regarded as a prognostic indicator for outcomes after cardiac arrest. However, whether miR-124 participates in cardiac hypertrophy remains unclear. Therefore, our study aimed to determine the role of miR-124 in angiotensin II(AngII)-induced myocardial hypertrophy and the possible mechanism. Primary cultured rat neonatal cardiomyocytes(NCMs) were transfected with miR-124 mimics or inhibitor, followed by AngII stimulation. Quantitative RT-PCR, western blot analysis and determination of cell surface area of NCMs were used to detect the hypertrophic phenotypes. We observed that miR-124 was elevated in AngII-induced hypertrophic cardiomyocytes. Cell surface area of NCMs and mRNA expression of atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP) and Î²-myosin heavy chain (Î²-MHC), indicators of myocardial hypertrophy, were higher in NCMs transfected with miR-124 mimics in the presence of AngII. On the contrary, knockdown of miR-124 by its specific inhibitor could restore these courses. Furthermore, downregulation of miR-124 alleviated the increased protein level of endoplasmic reticulum (ER) stress markers 78-kDa glucose-regulated protein (Grp78) and calreticulin(CRT) in AngII-induced NCMs. In conclusion, our study shows that inhibition of miR-124 effectively suppresses AngII-induced myocardial hypertrophy, which is associated with attenuation of ER stress.